Macrophages and the development and progression of non-alcoholic fatty liver disease - Alabdulaali, Bader; Al-rashed, Fatema; Al-Onaizi, Mohammed; Kandari, Anwar; Razafiarison, Joanna; Tonui, Dorothy; Williams, Michayla R.; Blériot, Camille; Ahmad, Rasheed; Alzaid, Fawaz (Frontiers in Immunology, 2023)
The liver is the site of first pass metabolism, detoxifying and metabolizing blood arriving from the hepatic portal vein and hepatic artery. It is made up of multiple cell types, including macrophages. These are either bona fide tissue-resident Kupffer cells (KC) of embryonic origin, or differentiated from circulating monocytes. KCs are the primary immune cells populating the liver under steady state. Liver macrophages interact with hepatocytes, hepatic stellate cells, and liver sinusoidal endothelial cells to maintain homeostasis, however they are also key contributors to disease progression. Generally tolerogenic, they physiologically phagocytose foreign particles and debris from portal circulation and participate in red blood cell clearance. However as immune cells, they retain the capacity to raise an alarm to recruit other immune cells. Their aberrant function leads to the development of non-alcoholic fatty liver disease (NAFLD). NAFLD refers to a spectrum of conditions ranging from benign steatosis of the liver to steatohepatitis and cirrhosis. In NAFLD, the multiple hit hypothesis proposes that simultaneous influences from the gut and adipose tissue (AT) generate hepatic fat deposition and that inflammation plays a key role in disease progression. KCs initiate the inflammatory response as resident immune effectors, they signal to neighbouring cells and recruit monocytes that differentiated into recruited macrophages in situ. Recruited macrophages are central to amplifying the inflammatory response and causing progression of NAFLD to its fibro-inflammatory stages. Given their phagocytic capacity and their being instrumental in maintaining tissue homeostasis, KCs and recruited macrophages are fast-becoming target cell types for therapeutic intervention. We review the literature in the field on the roles of these cells in the development and progression of NAFLD, the characteristics of patients with NAFLD, animal models used in research, as well as the emerging questions. These include the gut-liver-brain axis, which when disrupted can contribute to decline in function, and a discussion on therapeutic strategies that act on the macrophage-inflammatory axis.